USE OF IONIZATION IN TECHNOLOGICAL PROCESSES - BURLAKA, SERHIY; BORETSKA, TETYANA; SYVAK, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article examines the use of ionization in various technological processes and its impact on increasing efficiency, quality and environmental safety. Ionization, as a physical process, is becoming an increasingly popular technology due to its ability to improve productivity and reduce costs in a variety of industrial, agricultural, water treatment, and material processing industries.Studies show that ionization significantly increases the efficiency of air and water purification, reducing the concentration of harmful substances and pathogens to safe levels. In the agricultural sector, ionization helps to increase yield, improve the health of plants and animals, and also increases the resistance of products to microbiological deterioration. In industrial processes, such as coating, ionization allows to achieve greater adhesion and durability of coatings, which helps to increase the life of products.The article also discusses modern achievements in the field of ionization and their implementation in practice, which allows to reduce energy costs and minimize the environmental impact of technological processes. Research results demonstrate that ionization is a promising technology for a wide range of applications, from industrial production to environmental and medical applications.Despite the many advantages, the article emphasizes the need for further scientific research in this area to expand the possibilities of using ionization, especially in the fields of nanotechnology, biomedicine and alternative energy. The authors conclude that ionization can become a key technology of the future, able to significantly influence the development of the industry and ensure sustainable development in various industries. Thus, ionization is not only a powerful tool for improving existing technological processes, but also a promising direction for creating new, more efficient and environmentally safe solutions in production, the agricultural sector, and other spheres of activity.
Keywords: ionization; process; line; production; technologies